The Reorientation of Marriage Registration in the Compilation of Islamic Law: Shifting from Administrative Formality to Legal Obligation - Nugraha, Iqbal Subhan; Aziz, Abdul (AJIS: Academic Journal of Islamic Studies, 2025)
Marriage registration in Indonesia continues to be perceived merely as an administrative formality rather than a binding legal duty, leading many couples to neglect it. This condition results in an imbalance that weakens legal protection for women and children, particularly in cases of serial or unregistered marriages. This study examines the urgency of marriage registration from the perspectives of Islamic law and national law, and its implications for protecting family rights. Employing a qualitative methodology with normative and sociological legal approaches, this research also incorporates policy analysis of marriage registration practices in several Islamic countries. The findings demonstrate that marriage registration plays a strategic role in ensuring legal certainty, safeguarding the rights of women and children, and maintaining social order. From the perspective of the maqāṣid al-sharīʿah, marriage registration serves as a crucial instrument for protecting lineage (ḥifẓ al-nasl) and preventing injustice within the family. Accordingly, this study underscores the urgent need to reform the Compilation of Islamic Law (KHI) and strengthen public legal education to raise awareness of the importance of marriage registration. These findings affirm that marriage registration should be recognized as a binding legal obligation that extends beyond administrative purposes and constitutes a fundamental element of family law protection in Indonesia.